Timber Production Potentials in Nepal: A Critical Review on Projected Estimates - Dangi, Resham (Journal of Forest and Livelihood, 2024)
This paper delves into historical efforts to enhance timber production in the country. It examines the influence of spatial dynamics, public infrastructure facilities, processing industries, timber taxes, and timber export duty in timber production and supply. It contends that it must consider the critical constraints outlined in the policy documents and practiced standards when examining forecasted timber production potentials. The paper concludes that the aggregate annual timber supply in the market will likely reach 2.7 million m3, which will meet the demand for domestic timber and replace imported timber in the market.